Bibliogammers Report. 11-17 Março 2019 Report. Document produced for the Horizon 2020 project ‘ROCK’ - Falanga, Roberto (2020)
Bibliogamers 2019 was an event that aimed to promote information and knowledge about the history and heritage of the Marvila territory through a series of educational activities related to the conception and programming of videogames. The majority of the initiatives took place in the Marvila Library, with some special seminars directed particularly to media and technology students at the nearby D. Dínis secondary school. All of the activities were free and most of them were open to the wider public. Only some workshops and the Game Jam required the inscription of the participants.